Validity Analysis of the OIPE Model Teaching Materials with Experimental Methods to Train Critical Thinking Skills of Elementary School Students - Khasna, Fenny Tanalinal; Nuriyah, Nuriyah (Jurnal Penelitian Pendidikan IPA, 2023)
This research was conducted with the aim of obtaining experimental method-oriented OIPE science teaching materials that were suitable to be used to train critical thinking skills and science process skills for elementary school students. The research method used in this study refers to the 4-D development model. The results showed that the results of the development of teaching materials were feasible to be used in elementary school science learning with the following results: the syllabus got a score of 3.7 (very valid), lesson plans got a score of 3.8 (very valid). Validation of teaching materials on the feasibility aspect of content gets a score of 3.8 (very valid), the aspect of presentation feasibility gets a score of 3.7 (very valid), the feasibility aspect of language according to BSNP gets a score of 3.6 (very valid), the aspect of assessing teaching materials with the experimental method-oriented OIPE model gets a score 3.8 (very valid), the feasibility aspect of graphics gets a score of 3.8 (very valid), critical thinking test questions get a score of 3.52 (valid). From the validation results, it can be concluded that the teaching materials to be developed are very suitable for use in elementary school science learning